Nonalcoholic Fatty Liver Disease in Children - Mann, Jake P.; Valenti, Luca; Scorletti, Eleonora; Byrne, Christopher D.; Nobili, Valerio (Seminars in Liver Disease, 2018)
Nonalcoholic steatohepatitis, a progressive form of nonalcoholic fatty liver disease (NAFLD), is one of the most common hepatic diseases in children who present with particular risk factors including obesity, sedentary lifestyle, and/or a predisposing genetic background. The worldwide prevalence of NAFLD in children is a worrying phenomenon because this disease is closely associated with the development of both cirrhosis and cardiometabolic syndrome in adulthood. To date, the etiopathogenesis of primary NAFLD in children is unknown. Understanding the pathogenetic mechanisms provides the basis to characterize early predictors of the disease and noninvasive diagnostic tools and to design novel specific treatments and possible management strategies. Despite a few clinical trials on the use of antioxidants combined with lifestyle intervention for NAFLD, no treatment exists for children with NAFLD. In this review, the authors provide an overview of current concepts in epidemiology, histological features, etiopathogenesis, diagnosis, and treatment of NAFLD in pediatric population.
Keywords: NAFLD; obesity; children; NASH